Executive Remuneration in Chinese high-tech Enterprises and its Relevance to Firm performance - Wang, Shiyi (2020)
The 20th century is the era of knowledge, enterprise competition is fundamentally talent competition. A sound salary system is a powerful guarantee to attract, motivate and retain talents. Executive remuneration and firm performance is a broad topic. This paper aims to provide a supplement to the existing literature on industry segmentation. This study takes 1,182 Chinese high-tech listed companies as samples, selects relevant data from 2015 to 2019 for regression analysis, and studies the relationship between executive remuneration and firm performance, as well as the key corporate governance mechanisms that influence executive remuneration. The regression results of the three models are different, which indicates that the influence of firm performance on executive remuneration is not clear. The results also show that enterprise size variables and firm governance variables have a significant impact on the determination of executive remuneration. Through empirical analysis, this paper examines the current status of the "remuneration-performance" contractual relationship between senior executives in high-tech enterprises. It reveals the internal law and effect of the executive remuneration incentive system in China's high-tech enterprises. This is conducive to a more comprehensive understanding of China's high-tech enterprise executive remuneration system is conducive to further research and improve the remuneration system of China's high-tech enterprises.